Review on recent progress of lead-free halide perovskites in optoelectronic applications. (February 2021) - Li, Jiabao; Duan, Jialong; Yang, Xiya; Duan, Yanyan; Yang, Peizhi; Tang, Qunwei
Abstract: In the last decade, organic–inorganic hybrid lead-halide perovskites have been attracted tremendous attentions in the photovoltaic and optoelectronic community. Especially for perovskite solar cells (PSCs), the certified efficiency is up to as high as 25.5%, which has surpassed polycrystalline silicon solar cells and is comparable to the monocrystalline silicon solar cells. Till now, although the chemical instability of perovskite has been well alleviated by optimizing the lattice structure, the detrimental lead element is still a challenge for the commercialization process of PSC devices. To effectively resolve this issue, lead-free halide perovskites (LFHPs) have gained growing attentions recently due to their theoretically excellent optoelectronic properties and eco-friendly feature. With the aim to promote the development of LFHPs, in this review, we have mainly summarized the recent advancement of various LFHP materials and their applications in photovoltaics, light-emitting diodes (LEDs), photodetectors and other devices. Strategies for stabilization of perovskite lattice and performance improvement of optoelectronic devices including fabrication technology, compositional engineering and interfacial optimization are also emphasized. Finally, the potential and challenges of LFHPs are further discussed, providing new research direction for future development. Graphical Abstract: ga1 Highlights: This review covers the hot top of Pb-free perovskites for optoelectronic devices. Different elements can be employed to replace lead atoms in perovskite lattice. Strategies for improving the performance and stability are summarized. A brief outlook, including the remained issues and challenge is proposed.